2019
DOI: 10.2147/phmt.s231608
|View full text |Cite
|
Sign up to set email alerts
|

<p>Proximate Determinants of Under-Five Mortality in Ethiopia: Using 2016 Nationwide Survey Data</p>

Abstract: IntroductionAlthough there has been a remarkable decline in under-five mortality through the decades, it is still highest in socio-economically disadvantaged countries, including Ethiopia. The benefits of reducing under-five mortality have been highly emphasized in the ambitious target of Sustainable Development Goals. The risk factors of under-five mortality have not been exhaustively researched in Ethiopia using recent nationwide survey data.ObjectiveThis study aimed to determine the risk factors of under-fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
33
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 12 publications
13
33
3
Order By: Relevance
“…Average child size at birth ((0.68), (0.51, 0.90) prevent under-ve daughters mortality than very large daughters at birth. This agreed with a study derived from the 2016 EDHS data (5,30,34).Unplanned birth ((1.70), (1.03, 2.81) increase the likelihood of sons death than planned births. This contradict with a study that reported a preventive association (26).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Average child size at birth ((0.68), (0.51, 0.90) prevent under-ve daughters mortality than very large daughters at birth. This agreed with a study derived from the 2016 EDHS data (5,30,34).Unplanned birth ((1.70), (1.03, 2.81) increase the likelihood of sons death than planned births. This contradict with a study that reported a preventive association (26).…”
Section: Discussionsupporting
confidence: 89%
“…The former studies were a nationwide studies but the current study consider the poorest regions in Ethiopia that might contribute for the highest prevalence of under-ve child mortality. The prevalence of under-ve mortality in the pastoralist regions arehigher than the 2016 EDHS based studythat reported 6.7% (5). The difference might be as a result of socio-demographic difference between the pastoralist regions and the wider community, Ethiopia.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…We screened titles and abstracts for relevance; duplicates were removed, and then we analysed the full-text potentially relevant articles assessed for inclusion and exclusion criteria. For African content division geographically, according to the united nation statistics division schemes, for the geographic region of East Africa, the countries are named Burundi, Comoros, Djibouti, Eritrea, Ethiopia, Kenya, Madagascar, Malawi, Mozambique, Rwanda, Seychelles, Somalia Tanzania, Uganda, Zambia, Zimbabwe, South Sudan, and Sudan [ 11 ].…”
Section: Methodsmentioning
confidence: 99%